Molecular therodynamics and transport phenomena complexities and scales in space and time - Peters Michael H (New York McGraw-Hill, 2005)
Many newly developing fields of science and engineering, including nanotechnology, protein engineering, microfluidics, etc., require an in-depth molecular understanding and description of matter. Molecular Thermodynamics and Transport Phenomena: Complexi
Keywords: Mechanics; Space and time; Thermodynamic equilibrium; Transport theory